Robust Reed Solomon Coded MPSK Modulation - Emir M. Husni (LPPM ITB, 2010)
In this paper, construction of partitioned Reed Solomon coded modulation (RSCM), which is robust for the additive white Gaussian noise channel and a Rayleigh fading channel, is investigated. By matching configuration of component codes with the channel characteristics, it is shown that this system is robust for the Gaussian and a Rayleigh fading channel. This approach is compared with non-partitioned RSCM, a Reed Solomon code combined with an MPSK signal set using Gray mapping; and block coded MPSK modulation using binary codes, Reed Muller codes. All codes use hard decision decoding algorithm. Simulation results for these schemes show that RSCM based on set partitioning performs better than those that are not based on set partitioning and Reed Muller Coded Modulation across a wide range of conditions. The novel idea here is that in the receiver, we use a rotated 2^(m+1)-PSK detector if the transmitter uses a 2^m-PSK modulator.